1988
DOI: 10.1177/030098588802500407
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Hepatoblastomas: A Histologic, Ultrastructural, and Immunohistochemical Study

Abstract: Abstract.Hepatoblastomas from B6C3F1 and BALB/c mice were examined by light and electron microscopy and by immunohistochemical reactions for alpha-fetoprotein, keratin, and vimentin. Tumors occurred in one group of a chronic bioassay for the interaction of diet, genetic strain, and the carcinogen, 2-acetylaminofluorene. Tumors had several populations (including epithelial and mesenchymal cells) in various stages of differentiation. Neoplastic epithelial cells had features of embryonal hepatocytes, such as spar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
2
31
2
Order By: Relevance
“…The reason for the discrepancy with the present results remains unclear, but the negativity of our mouse HBs for keratin, predominantly of higher molecularweight, might point to their being less-differentiated. Unlike to human HBs which are observed only in infancy or childhood, mouse HBs are usually observed at the latestage of chemical hepatocarcinogenesis studies and seem to grow later than HCAs or HCCs [3,5,19,32]. In this study, nearly half of HBs were observed in and/or adjacent to HCAs or HCCs, in line with the previous reports suggesting an origin from hepatocellular lineage.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The reason for the discrepancy with the present results remains unclear, but the negativity of our mouse HBs for keratin, predominantly of higher molecularweight, might point to their being less-differentiated. Unlike to human HBs which are observed only in infancy or childhood, mouse HBs are usually observed at the latestage of chemical hepatocarcinogenesis studies and seem to grow later than HCAs or HCCs [3,5,19,32]. In this study, nearly half of HBs were observed in and/or adjacent to HCAs or HCCs, in line with the previous reports suggesting an origin from hepatocellular lineage.…”
Section: Discussionsupporting
confidence: 90%
“…In the present immunohistochemical examinations, mouse HBs were found not to react with antibodies against keratin, AFP, ALB or vimentin. Nonoyama et al [19] earlier reported 7 of 16 mouse HBs with squamous metaplasia to show positive reactions for keratin. Differentiation into ductal structures has also been described [12,20].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations